Extremal Functions for Trudinger-Moser Type Inequalities in ℝN (Journal of Partial Differential Equations, 2018)
Let $N≥ 2$, $α_N=Nω_{N-1}^{1/(N-1)}$, where $ω_{N-1}$ denotes the area of the unit sphere in $\mathbb{R}^N$. In this note, we prove that for any $0
Keywords: Extremal function; Trudinger-Moser inequality